Purinergic P2X7 receptor functional genetic polymorphisms are associated with the susceptibility to obesity in Chinese postmenopausal women. Issue 3 (March 2018) - Liu, Xingzi; Rao, Shenqiang; Gong, Chengxin; Li, Tao; Ding, Lu; Wang, Shuo; Zhong, Peipei; Wang, Jihong; Zhao, Jiani; Zhou, Yuru; Xiong, Chaopeng; Tu, Yunming; et al.
Abstract: Objective: We conducted a case-control study to investigate the associations of functional single-nucleotide polymorphisms in the purinergic P2X7 receptor (P2X7R) gene (rs2393799, rs7958311, rs1718119, rs2230911, and rs3751143) with obesity and overweight in a population of Chinese postmenopausal women. Methods: Our study included 180 obese women, 179 overweight women, and 204 controls. All participants were genotyped at the P2X7R rs2393799, rs7958311, rs1718119, rs2230911, and rs3751143 loci via allele-specific polymerase chain reaction (PCR) and PCR-restriction fragment length polymorphism procedures. The relationships between P2X7R genetic polymorphisms and their associated haplotypes with obesity (body mass index [BMI] ≥30 kg/m 2 ] and overweight (25 kg/m 2 ⩽ BMI < 30 kg/m 2 ) were evaluated. Results: Our results showed that P2X7R rs2230911G and rs1718119A were associated with an increased risk of obesity; in particular, both carriers of the rs2230911G allele and GG/(CG + GG) genotypes (G vs C, P < 0.001, odds ratio [OR] 2.87, 95% confidence interval [CI] 1.98-4.16; GG vs CC, P < 0.001, OR 8.76, 95% CI 3.29-23.35; CG + GG vs CC, P < 0.001, OR 2.54, 95% CI 1.63-3.95) and carriers of the rs17181191A allele and GA/(GA + AA) genotypes (A vs G, P < 0.001, OR 2.97, 95% CI 1.86-4.74; GA vs GG, P = 0.001, OR 2.72, 95% CI 1.55-4.79; GA + AA vs GG, P < 0.001, OR 3.05, 95% CI 1.79-5.19) were at a higher risk of obesity. No association with obesity or overweight was observed for the other three P2X7R polymorphisms (rs2393799, rs7958311, and rs3751143). Haplotype analysis indicated that P2X7R rs1718119A-rs2230911G-rs3751143C appeared to be a significant risk haplotype with obesity ( P = 0.0005, OR 2.37, 95% CI 1.45-3.90). Conclusions: P2X7R functional genetic polymorphisms and their estimated haplotypes are associated with obesity in Chinese postmenopausal women. Abstract : Supplemental Digital Content is available in the text